Beji Antaboga As A Symbol of Diversity: Tolerance and Integration Embodiment to Social Studies Learning - Moh. Imron Rosidi; Disman; Kokom Komalasari; Erlina Wiyanarti (Kamaya: Jurnal Ilmu Agama, 2023)
The writing of this article departs from intolerance problem that still often encountered, such as students who only want to make friends with friends of the same religion, not respecting and appreciating differences between friends and the lack of concern of students for peers. This is expected to be overcome if students learn Beji Antaboga material as a symbol of tolerance in Social Studies Learning. The purpose of this article is to find out the utilization of Beji Antaboga as material in social studies learning. The problems studied in this paper are (1) Why Beji Antaboga can be said as a form of tolerance between religious communities? (2) How to integrate Beji Antaboga into social studies learning? The method used in this research is a literature study, where the required materials/data are obtained from the library, both books, documents, journals, encyclopedias, articles and others. The results showed that Beji Antaboga is a pine forest area where existed different worshipping places for six official religions in Indonesia. It represents a tolerance attitude in Beji Antaboga. The existence of the religious tolerance in Beji Antaboga can be integrated into social studies learning for class IV students, the odd semester on study material about Diversity of Ethnicity and Culture by using a field trip method.